Expansion vessel for supercritical hydrogen in a spallation neutron source moderator circuit. Issue 1 (November 2015) - Klaus, M; Eisenhut, S; Quack, H; Haberstroh, C; Bessler, Y
Abstract: High-energy neutrons are being decelerated by passing through supercritical parahydrogen circulated by pumps in a closed loop. Fluctuations in neutron heat load cause changes of the circuits' local and average temperature and hence significant pressure variations caused by the almost incompressible behavior of hydrogen. Solutions by adding a variable volume in form of a helium gas-backed metal bellow to mitigate pressure deviations are already in use. This paper presents an alternative approach by introducing a vertical storage vessel for supercritical hydrogen in a side branch of the moderator loop, with cold incompressible high density hydrogen at the bottom and warmer compressible lower density hydrogen at the top.